Comparative cellular immune response study of anthraxin prepared by a modified method with antigens extracted from Bacillus anthracis: An’am J.L. Al-Juboury, Zahid S. Aziz and Ghazi M. Al-Khatib - Al-Juboury, An’am J.L. (The Iraqi Journal of Veterinary Medicine, 2008)
The study was aimed to comparison of anthraxin prepared by a modifiedmethod from cell-wall extract of avirulent B .anthracis strain 34F2(Sterne)with antigens extracted from the same strain as 1/40 antigen, autoclaved 1/40and the crude toxin. These antigens were compared on their induction of cellmediatedimmunity (CMI) in guinea pigs. Animals were immunized andboosted subcutaneously with the Sterne live veterinary anthrax vaccine. Twoweeks after the booster dose, animals were skin-tested with the four antigens.Anthraxin was the most active antigen which recorded 16.66 mm a mean oferythema and 2.3 mm a difference of skin thickness after 24 hours. Both 1/40and autoclaved 1/40 antigens gave approximately the same results whichwere 12.5 mm as a mean of erythema and 2.25 mm skin thickness for thefirst one; and 12.8mm ,1.66mm for the other respectively. The toxin showedthe lowest results of erythema 7.8 mm with edema. These antigens were alsocompared according to the histological changes on their sites of inoculation.Marked (typical) picture of delayed type of hypersensitivity (DTH) reactionwas occurred for anthraxin